(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
This study sought to understand how Arabic language teachers in Al-Anbar Governorate utilize authentic assessment methods, drawing insights from both teachers and educational supervisors. These methods encompass performance assessment, portfolio assessment, interviews, observation, self-assessment, peer assessment, and written tests. Employing a descriptive research approach, the study utilized a detailed questionnaire of 44 items, categorized into seven domains, to gather data. The sample included 185 individuals, consisting of 155 teachers (representing 10% of the total population) and 30 educational supervisors, selected randomly. The findings indicated a moderate overall use of authentic assessment methods by teachers. Among the domains, "portfolio assessment" emerged as the most commonly employed method, with a mean score of 3.02, while "peer assessment" was the least utilized, scoring an average of 1.84. Statistically significant differences were observed between teachers and supervisors, with supervisors demonstrating a higher frequency of using authentic assessment techniques. These variations were largely attributed to inadequate field training, limited resources, and an overreliance on traditional tests by teachers. The study advocates for the implementation of robust training programs aimed at equipping teachers with the necessary skills to effectively apply authentic assessment methods. Furthermore, it suggests integrating these approaches into curricula to enhance educational quality. The adoption of such practices is expected to foster students’ critical thinking abilities and improve overall educational outcomes. These results underscore the urgent need for advancing teaching strategies in Arabic language education to promote more inclusive and effective learning environments.